FAKTOR PENGHAMBAT EFEKTIVITAS PENYELENGGARAAN PENDIDIKAN KHUSUS DIKOTA PEKANBARU - Aldeana, Riska; ", Adianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
National education functions to develop ability and shape character and civilization nationâ€™s with dignity in order to educate the life of the nation, purpose at developing the potential of students to become human beings who believe in and fear God Almighty, have good morality, be healthy, have knowledge, be skilled, be creative, be independent and become democratic and responsible citizens. Based on Provincial Regulation Number 5 article 20 of 2018 concerning Implementation of Special Education, Special Education is education for students who have difficulty in participating in the learning process because of physical, emotional, intellectual, mental, social disorders, and have special intelligence and talent potential. The phenomenon in this study is that there are still many children with special needs who are not in school. The purpose of this assessment is to find out how the effectiveness of the implementation of special education policies in the city of Pekanbaru and to determine the inhibiting factors for the effectiveness of the implementation policy. This research was conducted in Pekanbaru City using qualitative descriptive methods, data collected through interviews, observation and documentation. This is shown by the love ibterest of the community to send their children to schoolÂ Keywords : Effectiveness, Implementation, Special Education